From theorization about teaching-learning to the practice in nursing continuing education and your contribution to self-efficacy (Research, Society and Development, 2019)
The objective of this study was to know and problematize the explanatory theories about the learning process, focusing on the use of a teaching methodology based on experiential learning, called in situ simulation, and the relation of the result of this experience to the level of professional confidence to perform cardiopulmonary resuscitation. An exploratory quantitative approach was conducted, where the participants were divided into 3 groups with different intervention periodicities. A questionnaire based on a Likert-type scale on agreement level investigated the participants' perceptions regarding their competencies in attending to cardiorespiratory arrest before and after participating in each in situ simulation. It was evidenced averages of self-confidence of the highest professionals in the post-simulation evaluation, compared to the pre-simulation in most of the groups. It has been found that the fact that a learning methodology promotes practice within the professional's work context, and provides immediate feedback of its performance, can improve the professional's confidence, and when it causes discomfort for ineffective performance, promotes reflection and motivates future improvements. The use of in situ simulation in the nursing continuing education has shown potential for experiential learning, where, from the experimentation of a situation in a real context of the service, one can observe the increase of the self-efficacy of the apprentices.